An Experimental Study of the Application of Gravitational Search Algorithm in Solving Route Optimization Problem for Holes Drilling Process - Omar, Norhaizat; Eng, Chieh Ong; Adam, Asrul; Hasim, Saipol Hadi; Zainal Abidin, Amar Faiz; Jaafar, Hazriq Izzuan; Zakaria, Hamzah; Hassan, Jefery; Nordin, Nur Anis; Osman, Khairuddin; Mohd Hussein, Shamsul Faisal (2014)
Previously, route planning in holes drilling process has been taken for granted due to its automated process, in nature. But as the interest to make Computer Numerical Control machines more efficient, there have been a steady increase in number of studies for the past decade. Many researchers proposed algorithms that belong into Computational Intelligence, due to their simplicity and ability to obtain optimal result. In this study, an optimization algorithm based on Gravitational Search Algorithm is proposed for solving route optimization in holes drilling process. The proposed approach involves modeling and simulation of Gravitational Search Algorithm. The performance of the algorithm is benchmark with one case study that had been frequently used by previous researchers. The result indicates that the proposed approach performs better than most of the literatures.